(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Employee performance in a variety of businesses is now significantly influenced by emotional intelligence (EI). Understanding the connection between EI variables and bank employee performance is the main goal of this study. A standardised questionnaire that assessed emotional intelligence (EI) traits like self-awareness, self-regulation, motivation, empathy, and social skills was used to gather data from a sample of 150 bank employees. The main aim of present research is to study components of emotional intelligence and its influence on employees work performance confined to private banks. A self-assessment questionnaire was administered to a sample of 150 private bank employees as part of the study in order to gauge their levels of emotional intelligence, its components (EI) and its influence on performance of bank employees.